La toma de decisiones en la gestión administrativa de la empresa Arsaico cía. ltda. cantón Chambo, período 2016 - Zambrano Andrade, Luis Fernando (2018)
In the present investigation called "The decision making in the administrative management of the company Arsaico Cía. Ltda. Cantón Chambo, 2016 period, an evaluation was carried out in order to identify the possible problems that exist within the company and thus be able to correct them. To identify these problems, objectives were set that helped us to have enough evidence to be able to sustain them, and the state of the art was developed where, basically, all the antecedents are detailed, the theoretical bases related to the research. In the methodology all the methods used in the investigation are captured, which, through surveys, indicators, flow grams etc. they provided us with sufficient and competent results to be able to reach the discussion and thus be able to issue the respective conclusions and recommendations.